Child sexual abuse in Zimbabwe: an agenda for social work - Muridzo, Noel G. (2020)
The problem of child sexual abuse (CSA) continues to be a serious concern in Zimbabwe. This is demonstrated by the numerous newspaper articles that continue to highlight the problem. This article explores the problem, factors that predispose children to the problem and the impact of child sexual abuse on the child. It argues that strong Zimbabwean cultural practices are among the factors that expose children to CSA and that the social work profession has a role to play in dealing with the social ill and in the protection of children. It is argued that social work intervention should move beyond the ‘business as usual approach’ the remedial approach to the problem and assume robust complimentary proactive developmental approaches. The approach should thus confront the status quo of the strong cultural practices, to contain the problem. The remedial approach is none the less important to deal with the effects on the child survivors.